2015
DOI: 10.4995/wrs.2015.3551
|View full text |Cite
|
Sign up to set email alerts
|

Effect of human menopausal gonadotropin on testicular morphometry, gonadal and extragonadal sperm reserves of rabbit bucks

Abstract: Testicular morphometry, gonadal and extragonadal sperm reserves of rabbit bucks treated with Human Menopausal Gonadotrophin (Menogon ® ) were studied. Twenty-four crossbred rabbit bucks weighing 1.3-1.6 kg at 15-17 wk were randomised into 4 treatment doses of 0 (control), 7.5, 15.0, and 22.5 I.U. in a completely randomised design with 6 bucks per group. A vial of Menogon ® was reconstituted in 1 mL of physiological saline solution and administered intramuscularly at 72 h intervals for 56 d prior to commencemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…The result on body weight gain followed a somewhat similar trend with the result of semen concentration, motility, viability, libido and epididymis weight observed in this study. This is in line with the report of Bezerra et al (2009) and Ansa and Imasuen (2015) who observed a positive correlation between body weight and reproductive indices.…”
Section: Controlsupporting
confidence: 93%
“…The result on body weight gain followed a somewhat similar trend with the result of semen concentration, motility, viability, libido and epididymis weight observed in this study. This is in line with the report of Bezerra et al (2009) and Ansa and Imasuen (2015) who observed a positive correlation between body weight and reproductive indices.…”
Section: Controlsupporting
confidence: 93%